Active hydrothermal vent ecosystems in the Indian Ocean are in need of protection - van der Most, Naomi; Qian, Pei-Yuan; Gao, Yan; Gollner, Sabine (Frontiers in Marine Science, 2023)
Deep-sea hydrothermal vent fields are among the most pristine and remarkable ecosystems on Earth. They are fueled by microbial chemosynthesis, harbor unique life and can be sources of precipitated mineral deposits. As the global demand for mineral resources rises, vent fields have been investigated for polymetallic sulfides (PMS) and biological resources. The International Seabed Authority (ISA) has issued 7 contracts for PMS exploration, including 4 licenses for vent fields in the Indian Ocean. Here, we provide a summary of the available ecological knowledge of Indian vent communities and we assess their vulnerability, sensitivity, ecological and biological significance. We combine and apply scientific criteria for Vulnerable Marine Ecosystems (VMEs) by FAO, Particular Sensitive Sea Areas (PSSAs) by IMO, and Ecologically or Biologically Significant Areas (EBSAs) by CBD. Our scientific assessment shows that all active vent fields in the Indian Ocean appear to meet all scientific criteria for protection, and both the high degree of uniqueness and fragility of these ecosystems stand out.